Varied shoot growth in rice plants across different developmental stages under induced flooding - Samanta, Pratyasha; Chakrabarti, Abhra; Dey, Narottam (Plant Science Today, 2021)
All the modern high yielding rice varieties precariously respond to flooding, although a number of landraces are tolerant to wide range of flooding with penalty of low yield. Stage-specific flood tolerance experiment was performed at three different conditions for three different growth stages from germination to vegetative stage for five such selected landraces, along with a flood-resistant quiescent variety (FR13A), a sensitive line (IR42), an improved cultivar (Swarna) and one Sub1 loci introgressed improved line (Swarna-Sub1). Different morpho-physiological traits at each stage were observed and genotypes were evaluated by these quantifiable traits to understand their underwater performance. All the studied landraces represented strong seed germination and faster coleoptile elongation than FR13A, Swarna and Swarna-Sub1 under water. At early seedling stage var. Kumrogarh embraced with highest number of seedlings with leaves and extended greater leaf portion above the water. Shoot elongation associated with internodal and petiole/blade elongation and well developed aerenchyma tissue facilitated vegetative tissues to survive. In this stage, Kumrogarh had highest plant height but Bakui had highest internodal length which indicated that kumrogarh might have the greater leaf sheath or blade elongation up to day 21 and also smaller increase (%) in air cavity formation at day 21 which made the stem to be upright devoid of lodging. All these results indicated that the studied landraces are the potential resources for submergence avoiding response for all the stages and should be elaborately investigated for future breeding programme. The rice line kumrogarh may be one of the potent traditional rice which can withstand all sorts of submergence by virtue of all the stage-specific attributes under submergence stress.